Effect of severe plastic deformation and post-annealing on the mechanical properties and bio-corrosion rate of AZ31 magnesium alloy - Bin, Bryan Shi Jie (2018)
In this work, the effect of fine grain sizes on the mechanical and bio-corrosion properties of AZ31 magnesium alloy was studied. Bio-corrosion refers to the accelerated degradation of metal within the human body. Fine-grained (~1.5 µm) AZ31 was obtained through Severe Plastic Deformation (SPD) via three cycles of Constrained Groove-Pressing (CGP) under elevated temperature. The effects of CGP and post-annealing (at 473 K for 15 and 30 min) on bio-corrosion were preliminarily investigated by potentiodynamic polarization measurements and constant immersion tests. Results obtained show that the as-processed samples with annealing exhibited improvements in yield strength and ductility while the bio-corrosion rate in Hank’s solution remains fairly similar during the early stage.